Stress Response Variability in Preschoolers with Developmental Language Disorder: Genetic and Environmental Interactions - Syukrianti Syahda; Zakkiyatus Zainiyah; Dewi Anggriani Harahap (Postgraduate, University of Mataram, 2025)
Children with Developmental Language Disorder (DLD) show a high prevalence of psychological problems, yet understanding of individual variability in stress responses is limited. This study looked at how genetic and environmental factors affect stress responses in 200 preschool children (ages 3–6) from a PAUD in Bangkinang, Indonesia, including 100 with Developmental Language Disorder (DLD) and 100 without. Children with Developmental Language Disorder exhibited significantly greater cortisol reactivity (over 50% AUCi, p < .001), more pronounced decreases in heart rate variability (p < .001), and markedly higher anxiety spikes (p < .001) compared to control subjects. The multivariable regression analysis indicated a significant interaction between environmental and genetic variables (p < .001), collectively explaining 42% of the variation in cortisol reactivity. Cluster analysis revealed three distinct groups characterized by varying genetic and environmental risk factors: moderate responders (53%), severe stress (25%), and resilient individuals (22%). Our findings indicate that genetic and environmental factors interact in complex ways to alter the stress response of DLD, thereby supporting the development of intervention plans tailored to individual risk profiles.